Experimental investigation and modeling of diesel engine fuel spray - Kolodnytska, R. V.; Karimi, K.; Crua, C.; Heikal, M. R.; Sazhina, E. M. (НТУ "ХПИ", 2008)
A model for spray penetration in diesel engines is suggested. It is based on momentum conservation for a realistic mass flow rate transient profile. The modelling approach is based on tracking of centre-of-fuel-mass (COFM) of injected diesel fuel. The model was validated for Bosch and Delphi injectors using the data obtained at Sir Harry Ricardo automotive centre, University of Brighton, UK. The model is shown to produce a good agreement with the experimental data until major spray instability (such as cluster shedding). It has been found that the dispersion time (the adjustable model parameter) is increasing when injection pressure is decreasing. This follows the known tendency for spray breakup time.
Keywords: COFM model; apparatus; Model validation; procedures